Hubungan antara Pengetahuan tentang Menarche dengan Kecemasan Siswi - Adelia, Yolanda; Taufik, Taufik; Nurfarhanah, Nurfarhanah (Universitas Negeri Padang, 2013)
There are still many students who experience anxiety in the face of menarche. Anxiety often leads to wrong behavior customize. Anxiety occurs presumably because they lack knowledge about menarche. Target or Research: The first is to describe the student knowledge about menarche, and student anxiety. Second, to see relation with knowledge of student about menarche and dread of students. Quantitative research study was shaped by the kind of descriptive co relational. The population is student of class VII Junior High School Tanjung Gadang Sijunjung. The sampling technique used is proportional random sampling, totaling 61 students. Data were collecting using a questionnaire in the form of a graduated scale based on the Likert Scale. Data analysis techniques using Pearson Product Moment formula and processing data using the program Statistical Product and Service Solution for windows release 15.0. The research findings revealed that (1) knowledge of student about menarcheÂ are in the good category, (2) anxiety students are in the low category, (3) thereÂ is significant relationship between student knowledge about menarche with anxiety students with a correlation of -0,724 and a significance level of 0,000with a strong relationship level. Thus, it is suggested that BK teacher/School counselors can provide students with a complete knowledge of menarche. Such service like information service, content control services, service of counseling individual, and group counseling services.Keyword: Knowledge of menarche, Anxienty.